Carbon Dioxide Capture by Dendrimer-Modified Silica Nanoparticles - Bing Yu; Hailin Cong; Xiu Song Zhao; Zhaojing Chen (Adsorption Science & Technology)
Aminosilane- and dendrimer-modified silica nanoparticles were synthesized in the presence of (3-aminopropyl)trimethoxysilane and melamine-based dendrimer, respectively. The surface properties, morphology and carbon dioxide adsorption/desorption performances of the silica nanoparticles before and after surface modification were studied and compared. Severe aggregation of the silica nanoparticles was largely minimized after surface modification. The carbon dioxide adsorption capacity of the dendrimer-modified silica nanoparticles was significantly enhanced in comparison with the unmodified and aminosilane-modified silica nanoparticles because of the large surface area and presence of functional groups exhibiting CO 2 affinity in the former.